Studi Penggunaan Zink Anoda untuk Mengurangi Laju Korosi dalam Industri Perkapalan - Lekatompessy, Sonja Treisje Anthonia (Industrial Engineering Study Program, Pattimura University, 2025)
One way to reduce the rate of corrosion on ships is to use zinc anodes. The weight of the zinc anode plays an important role in determining how much zinc anode must be installed on the wet surface of the ship to withstand the rate of corrosion. This study aims to obtain protection against corrosion rates by analyzing data on the use of zinc anodes in the field and data on the use of zinc anodes from calculations. To determine the ability of the installed zinc anode, data on the last 5 years of corrosion rates from 3 ships and the amount of zinc anodes used each year are needed. The results obtained show that there was no addition of zinc anodes on ship 1 in the 4th year to the 5th year of 64,046 kg, the highest corrosion rate reached 0.1708 mm/year, while on ship 2, with the addition of zinc anode weight of 25,704 kg the corrosion rate decreased in the 5th year to 0.0317 mm/year. On ship 3 in the 4th year with the addition of zinc anode weight of 45,868 kg the corrosion rate decreased to 0.0138 mm/year.